Application of Brian Mulligan manual therapy method in headache treatment – case study = Zastosowanie metody Briana Mulligana w terapii bólu głowy – opis przypadku - Kochański, Bartosz; Kałużna, Anna; Kałużny, Krystian; Smuczyński, Wojciech; Hagner-Derengowska, Magdalena; Zukow, Walery; Hagner, Wojciech (Journal of Education, Health and Sport, 2016)
Kochański Bartosz, Kałużna Anna, Kałużny Krystian, Smuczyński Wojciech, Hagner-Derengowska Magdalena, Zukow Walery,Hagner Wojciech. Application of Brian Mulligan manual therapy method in headache treatment – case study = Zastosowanie metody Briana Mulligana w terapii bólu głowy – opis przypadku. Journal of Education, Health and Sport. 2016;6(1):101-106. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.44647 http://ojs.ukw.edu.pl/index.php/johs/article/view/44647 http://pbn.nauka.gov.pl/works/693458 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.12.2015. Revised 25.12.2015. Accepted: 09.01.2016. APPLICATION OF BRIAN MULLIGAN MANUAL THERAPY METHOD IN HEADACHE TREATMENT – CASE STUDY ZASTOSOWANIE METODY BRIANA MULLIGANA W TERAPII BÓLU GŁOWY – OPIS PRZYPADKU Bartosz Kochański1, Anna Kałużna1, Krystian Kałużny1, Wojciech Smuczyński2, Magdalena Hagner-Derengowska1,3, Walery Zukow4,Wojciech Hagner1 1 Katedra i Klinika Rehabilitacji, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu; 2 Klinika Neurochirurgii, Neurotraumatologii i Neurochirurgii Dziecięcej, Wydział Lekarski, Uniwersytet Mikołaja Kopernika w Toruniu; 3 Katedra Neuropsychologii, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu; 4 Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy; Summary Headache is a common occurrence in modern society. International Headache Society (IHS) classifies over 80 different kinds of headache. Spontaneous headaches might indicate dysfunction or disorder of cervical spine. The article presents the case of a 17-year-old patient suffering from cervicogenic headache. Diagnostic and therapeutic procedures using the Mulligan method have been discussed on the basis of the case study. The results, possibilities and unique biomechanical effect of SNAG (sustained natural apophyseal glides) techniques has also been presented. Streszczenie Bóle głowy są powszechnym zjawiskiem obserwowanym we współczesnym społeczeństwie. Klasyfikacja International Headache Society (IHS) wyróżnia ponad 80 różnych rodzajów bólów głowy. Szczególną uwagę należy zwrócić na samoistne bóle głowy, które mogą być związane z dysfunkcjami i zaburzeniami kręgosłupa w odcinku szyjnym. W pracy przedstawiono przypadek 17-letniego pacjenta z bólem głowy pochodzenia szyjnego. Na przykładzie opisanego przypadku omówiono postępowanie diagnostyczne i terapeutyczne z wykorzystaniem metody Mulligana. Zwrócono szczególną uwagę na efekty, możliwości oraz unikalny efekt biomechaniczny technik „SNAG” (sustained natural apophyseal glides). Key words: headache, Mulligan method, SNAG techniques. Słowa kluczowe: ból głowy, Metoda Mulligana, techniki SNAG.